DIAGNOSTIC COMPETENCE IN BONE TUMORS: INFLUENCE OF ONCO-ORTHOPEDIC TRAINING - Julia Pozzetti Daou; Caio Falk Giannotti; Jairo Greco Garcia; Marcelo de Toledo Petrilli; Dan Carai Maia Viola; Reynaldo Jesus Garcia Filho (Acta Ortopédica Brasileira)
Abstract Understanding the nature of musculoskeletal tumors is crucial for appropriate management and to secure a favorable prognosis. Orthopedists’ ability to identify these pathologies early and accurately is paramount. There is a requirement to raise awareness within the orthopedic community regarding the necessity of referrals to orthopedic oncology specialists, as delays in initiating proper treatment can compromise patient prognosis. Objective: The objective was to assess the capability of non-specialist orthopedists in identifying bone lesions suggestive of tumors and thus classify them by employing a questionnaire with radiographs and comparison with specialists. We aim to gain an in-depth understanding of their diagnostic competence and provide insights into teaching the subject in orthopedic residency programs. Methods: The sample consisted of 90 participants who answered the questionnaire: 18 orthopedic oncology specialists, 58 non-specialist orthopedists, and 14 orthopedic residents. Results: Specialists achieved an average accuracy of 12.50 ± 1.07, while non-specialists scored 10.00 ± 0.60 (p<0.001). Among non-specialists, there was no statistical significance when comparing whether they underwent specialization internship during residency nor the duration of the year of such training. The period since graduation also indicated no differences. Conclusion: This study highlights the importance of referring patients with suspected tumors to specialized orthopedists. Level of Evidence V; Expert Opinion.